Program Kader Kesehatan Jiwa terhadap Kecemasan, Stres dan Depresi pada Lansia - Nurzaman, Muchammad; Suryani, Suryani; Wisnusakti, Khrisna (Journal of Telenursing (JOTING), 2024)
This study aims to examine the effect of the mental health care mentoring program on anxiety, stress, and depression in the elderly. The research method used was a pre-experimental design with a one-group Pre-Post Test Design. The results of the study showed that the value of reducing anxiety in the elderly pre-test anxiety was 76 people (32.28%), and post-test anxiety was 52 people (22.4%). The stress reduction value in the elderly pre-test stress was 32 people (13.8%) and post-test stress was 14 people (6%). The value of reducing depression in the elderly, pre-test depression was 33 people (14.28%) and post-test depression was 21 people (9.1%). Meanwhile, the results of the Wilcoxon signed rank test showed that there was an influence because the p-value was 0.000, <0.05, which means there was an influence of cadre mentoring on anxiety, stress, and depression. In conclusion, there is an influence of cadre assistance on anxiety, stress, and depression in the elderly. Keywords: Depression, Elderly, Health Cadres, Anxiety, Mentoring Program, Stress.